Results of application of modular artificial neural networks for intelligent data analysis (data mining) and forecasting processes in the field of ecology and environment protection - Trokhymchuk, R.M. (Штучний інтелект, 2016)
The aim of this work is the use of modular artificial neural networks (ANN) for data mining (Data Mining) and forecasting of various processes in the field of ecology and environmental protection, as well as the comparison of the results of the proposed model with the results of other data analysis methods (the methods of mathematical modeling and mathematical statistics). Метою даної роботи є використання модульних штучних нейронних мереж для виведення даних та прогнозування різних процесів у галузі екології та охорони навколишнього середовища, а також порівняння результатів запропонованої моделі з результатами інших методів аналізу даних (методи математичного моделювання та математичної статистики).